(untitled) (Farabi Journal of Social Sciences, 2019)
Abstract. The paper aims measuring performance of the project of international transport corridor «West Europe-West China» in the Republic of Kazakhstan and propose ways for its development. Recognition of the role of international transport corridors (ITC) in the modern world has generated a large number of theoretical and applied researches. The nature of ITC, projects of their creation and their role in competitive advantages formation are the subject under consideration in works of commissions in different countries all over the world. The competitiveness of the economy and the state, in the context of globalization, given the vastness of the territory of Kazakhstan, will largely depend on the efficient operation of transport and communication complex.